2019
DOI: 10.3390/f10010062
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effect of Climate Change on the Potential Distribution of Qinghai Spruce (Picea crassifolia Kom.) in Qilian Mountains

Abstract: Qinghai spruce forests play a key role in water conservation in the dry region of northwest China. So, it is necessary to understand the impacts of climate change on the species to implement adaptation strategies. Based on the four-emission scenario (i.e., RCP2.6 (Representative Concentration Pathway), RCP4.5, RCP6.0 and RCP8.5) set by the Intergovernmental Panel on Climate Change (IPCC) fifth assessment report, in the study, we predicted the potential distribution of Qinghai spruce (Picea crassifolia Kom.) un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 71 publications
1
36
0
2
Order By: Relevance
“…Unfortunately, surface meteorological stations are sparse in QLM, especially in the western QLM. erefore, most of previous studies in QLM are based on limited observations or remote sensing data on the climate and glacier changes in QLM [6][7][8][9]. Jiang et al [10] found that the annual variations of ice and snow are significant along elevations based on MODIS data.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, surface meteorological stations are sparse in QLM, especially in the western QLM. erefore, most of previous studies in QLM are based on limited observations or remote sensing data on the climate and glacier changes in QLM [6][7][8][9]. Jiang et al [10] found that the annual variations of ice and snow are significant along elevations based on MODIS data.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research of different regions has reported variables found to have an important effect on various species. For example: Evangelista, Young & Burnett, 2013 Studied teff by using three climate projection model that the value of predictable were 0.79 (Bio16, Bio12, Bio19, Bio15) and others studied different species in different geographical area including, (Elham et al, 2015) (Bio2, Bio3, Bio7, Bio8, Bio13, Bio14, Bio15, Bio18), ( Ardestani et al, 2015 ) (Bio8, Bio19, Bio2, Bio13, Bio7), Sen et al, 2016 (Bio4 and Bio19), Rong et al, 2019 (Bio1, Bio8 and elevation), ( Abdelaal et al, 2020 ) (elevation, precipitation, temperature and soil), and Yang et al, 2020 (Temp Seasonality, Precipitation, Vegetation Type, Soil Type). Our results indicate that temperature of coldest quarter had a predictability value of 0.83 for teff, which is stronger than that of any other existing model.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of SDMs have been developed to predict species distributions under different climate scenarios (e.g., RCP). Commonly used SDM models including the Genetic Algorithm for Rule-set Production (GARP), BIOCLIM and Ecological Niche Factor Analysis (ENFA) have proved to be essential for predicting target species distributions under current, and also future climate scenarios ( Rong et al, 2019 ; Tognelli et al, 2009 ). Maxent (maximum entropy) has been widely used due to its many advantages, including its ability to: deal with incomplete data, small sample size, species presence data, both continuous and categorical environmental data; reduce laborious jobs in data collection; facilitate model interpretation, and for its prediction accuracy and reliability ( Guo et al, 2017a ; Rong et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many model intercomparison studies have reported that the MaxEnt model, which is based on the principle of maximum entropy [24,27,31,32] , typically outperforms other species distribution models (SDMs) in terms of high tolerance and high predictive accuracy [33][34][35] . Over the past 10 years, worldwide research teams have achieved excellent results in the study of rare animal and plant diversity protection [36][37][38][39] , invasive species risk prediction [40,41] , marine ecosystem protection [42,43] , disaster distribution prediction [44] , and disease propagation [45,46] using the MaxEnt model. Zhang et al [47] predicted the distribution of suitable habitats for Cinnamomum camphora (L.) Presl in China under future climate change scenarios.…”
Section: Introductionmentioning
confidence: 99%